Multiple Regulatory Levels of Growth Arrest-Specific 6 in Mucosal Immunity Against an Oral Pathogen - Nassar, Maria; Tabib, Yaara; Capucha, Tal; Mizraji, Gabriel; Nir, Tsipora; Saba, Faris; Salameh, Rana; Eli-Berchoer, Luba; Wilensky, Asaf; Burstyn-Cohen, Tal; Hovav, Avi-Hai (Frontiers in Immunology, 2018)
GAS6 expressed by oral epithelial cells and dendritic cells (DCs) was shown to play a critical role in the maintenance of oral mucosal homeostasis. In this study we demonstrate that the induction of pathogen-specific oral adaptive immune responses is abrogated in Gas6-/- mice. Further analysis revealed that GAS6 induces simultaneously both pro- and anti-inflammatory regulatory pathways upon infection. On one hand, GAS6 up-regulates expression of adhesion molecules on blood vessels, facilitating extravasation of innate inflammatory cells to the oral mucosa. GAS6 also elevates expression of CCL19 and CCL21 chemokines and enhances migration of oral DCs to the lymph nodes. On the other hand, expression of pro-inflammatory molecules in the oral mucosa are down-regulated by GAS6. Moreover, GAS6 inhibits DC maturation and reduces antigen presentation to T cells by DCs. These data suggest that GAS6 facilitates bi-directional trans-endothelial migration of inflammatory cells and DCs, whereas inhibiting mucosal activation and T-cell stimulation. Thus, the orchestrated complex activity of GAS6 enables the development of a rapid and yet restrained mucosal immunity to oral pathogens.